Pengaruh Implementasi E-Budgeting Terhadap Transparansi Keuangan Daerah Di Indonesia - Nasution, Dito Aditia Darma; Rizqy Ramadhan, Puja (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
This study aims to determine the effect of implementing e-budgeting on regional financial transparency in Indonesia. The theory used to achieve the objectives of this study is agency theory. This research was conducted at 32 local governments in Indonesia. Based on a simple regression model, this study shows that the implementation of e-budgeting has a positive and significant effect on regional financial transparency in Indonesia. These findings reinforce previous research. The findings of this study have implications in the form of useful contributions to government officials (executive and legislative), in demonstrating the important role of e-budgeting to encourage regional financial transparency. In addition, the findings of this study can be used as a basis for further research related to the topic of implementing e-budgeting and regional financial transparency. Keywords: E-Budgeting, transparency, regional finance